2017
DOI: 10.1016/j.biopha.2016.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of three new norditerpenoid alkaloids in vitro and potential mechanism via PI3K/Akt signaling pathway

Abstract: Diabetes is a metabolic disease with the characteristic of high blood glucose (hyperglycemia). In our previous study, we found that nigelladines A-C (compounds A-C), three norditerpenoid alkaloids from the seeds of Nigella glandulifera Freyn (Ranunculaceae) exhibited protein of tyrosine phosphatase 1B (PTP1B) inhibitory activity in vitro. In the present study, we further investigated their anti-diabetes activities in L6 moytubes and illuminated the mechanisms of action of compounds A-C. Several parameters of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 33 publications
1
36
0
2
Order By: Relevance
“…It is mainly found in people who are obese and hypertensive (high blood pressure). It is characterized by different kinds of metabolic disorders which is due to insulin deficiency or impaired insulin action [4]. It has been noted that type II DM has a high prevalence all over the world, with prevalent rate of about 366 million in 2011 [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly found in people who are obese and hypertensive (high blood pressure). It is characterized by different kinds of metabolic disorders which is due to insulin deficiency or impaired insulin action [4]. It has been noted that type II DM has a high prevalence all over the world, with prevalent rate of about 366 million in 2011 [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies reported that exogenous H 2 S contributed to the defense against oxidative damage [18], [19] and inhibition of apoptosis and the autophagy pathway [20], which are also related to regulating the aging process [21]. The PI3K/AKT pathway is commonly recognized as a key signaling pathway controlling autophagy [22] and metabolism [23], as well as oxidative stress. Thus, the PI3K/AKT signaling pathway could be a therapeutic target under some oxidative stress conditions, such as the process of aging.…”
Section: Introductionmentioning
confidence: 99%
“…In the research by Arun et al ., the cellular model was L6 myoblasts. These L6 skeletal muscle cells have been extensively used in recent investigations of phytochemical compounds with antidiabetic effects . This study used rosiglitazone (100 n m ) as a positive control and the entire inflorescence for the extractions.…”
Section: Resultsmentioning
confidence: 99%
“…These L6 skeletal muscle cells have been extensively used in recent investigations of phytochemical compounds with antidiabetic effects. [72,73] This study used rosiglitazone (100 nM) as a positive control and the entire inflorescence for the extractions. The L6 cells differentiated were pretreated with 50 and 100 lg/ ml methanol extract for 24 h, and were then washed with buffer and incubated with 2-NBDG (0.1 mM) for 30 min.…”
Section: Improvement In Glucose Uptakementioning
confidence: 99%